Annual Plan 1995-96 Vol. I General Profile and Sectoral Reviews Government of Uttar Pradesh State Planning Commission - Planning Commission (Planning Commission, 1995)
During the decade 1981-91, the increase in the number of workers in the state was 31.56% against an increase of 25.48 percent in its total population. The total number of workers moved up from 340.51 lakh in 1981 to 447.99 lakh in 1991, and the proportion of workers to the total state’s population from 30.7 to 32.2 percent. The share of workers in state’s population, at 32.2 percent is considerably lower than the corresponding figure of 37.5 percent at National level. The state, with 32.2 percent workers in the total population, ranked 7th among major states, after Andhra Pradesh (45.0 percent) Tamilnadu (43.3 percent), Maharashtra (43.0 percent), Madhya Pradesh (42.8 percent), Karnataka (42.0 percent) and Gujarat (40.2 percent). All these six states are ahead of U.P. in per capita income also. The states like Punjab, Haryana and Kerala having lower work participation ratio of 30.9 percent,31.0 percent and 31.9 percent respectively have also considerably, higher per capita state income. The above situation only indicates that U.P. suffers not only from the problem of insufficiency of employment opportunities but also from lack of comparatively more remunerative jobs. The share of total workers in rural population also moved up from 31.5 percent to 33.5 percent during the decade 1981-91. Similarly, the share of female workers in female population has also risen from 8.1 percent to 12.3 percent during the aforesaid decade of 1981-91. This is indicative of the efforts made to provide more job opportunities to the rural masses and to raise female work participation ratio have yielded some good results. The shares of workers in urban population however, slipped down from 27.3 percent to 27.1 percent. The share of male workers in male population also declined from 50.8 percent to 49.7 percent during the decade of 1981-91. The decline in the share of workers in urban areas and particularly among male population is a matter of concern and need special attention.
General Profile and Sectoral Reviews
Government of Uttar Pradesh